PENGEMBANGAN MEDIA PELAYANAN INFORMASI BERBASIS PREZI UNTUK KETERAMPILAN PENGAMBILAN KEPUTUSAN KARIER SISWA KELAS XII SMK NEGERI 1 CIBINONG - Rini Meilani; Ika Mustika; Siti Fatimah (FOKUS (Kajian Bimbingan & Konseling dalam Pendidikan), 2023)
This study aims to determine the feasibility of Prezi-based information services in students' career decision-making skills, in connection with Vocational High School (SMK) graduates who are prepared to become "BMW" namely work, continue education and entrepreneurship for students, then SMK students start to take career decisions seriously. This research uses research and development (R and D) methods. The subjects in this study were 10 class XII students of SMK Negeri 1 Cibinong. Product validity tests were carried out by product experts, material experts, practitioners in schools and student responses to Prezi-based information service media. The results showed that the development of Prezi-based career information service media products obtained 96% results, which means the research product has a feasibility in the very good category to be used in providing career information services. Keywords:Career Decision Making, Prezi, Information Services